Part 6: Pediatric Basic Life Support and Pediatric Advanced Life Support: 2015 International Consensus on cardiopulmonary resuscitation and emergency cardiovascular care science with treatment recommendations - de Caen AR (American Heart Association, 2019)
10.1161/CIR.0000000000000275